Antiproliferative activity from five Myrtaceae essential oils (Research, Society and Development, 2023)
The Myrtaceae plants are cultivated for their edible fruits and folk medicinal uses. Likewise, their leaves, flowers, and fruit essential oils (EOs) are described to have antiproliferative, antimicrobial, and antioxidant activities. This work analyzed the chemical compositions and evaluated the antiproliferative activities of essential oils (EO) of Myrcia bella Cambess, Myrcia fallax (Rich.) DC., Myrcia guianensis (Aubl.) DC., Eugenia aurata O. Berg, and Eugenia punicifolia (Kunth) DC, from the Brazilian Cerrado. EOs were obtained by leaf hydrodistillation and analyzed by Gas Chromatography-Mass Spectrometry (GC-MS) plus Gas Chromatography-Flame Ionization Detector (GC-FID). The major component in M. bella was α-cadinol (14.4%); in Myrcia fallax (Rich.) DC., guaiol acetate (14.4%); and in M.guianensis, (E)-iso-g‑bisabolene (17.5%). For E. aurata and E. punicifolia, bicyclogermacrene (25.3%) and (E)-caryophyllene (18%), respectively, were the most relevant chemical constituents. The EOs were tested against the human tumor cell lines UACC-62 (melanoma), MCF7 (breast), 786-0 (kidney), NCI-H460 (lung), OVCAR-3 (ovarian), HT29 (colon), and K562 (leukemia) and one non-tumor cell line (VERO). Eugenia aurata presented the most promising effect against HT29 (TGI = 1.5 mg/mL), K562 (TGI = 5.0 mg/mL), and no toxicity against non-tumor VERO cells (TGI> 250 mg/mL). For the other EOs, moderate to no activity was observed. So, in conclusion, E. aurata EOs revealed a good potential for anticancer applications.